The Kurdish question : Kurdistan and its relevance within the politics of the Middle East - Šmakal, Filip; Huntley, Matthew David; Kočí, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This thesis attempts to find out whether the formation of Kurdistan would be a viable solution to the Kurdish question and would stop the suffering of the Kurds of the three countries, which they have been subjected to for the past one hundred years. It does this using Constructivist theory to identify Kurdish identity and its struggles.
Vedoucí práce: Matthew David Huntley
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses